The effects of digital media buying on advertisers - Šehić, Lejla (Array, 2020)
Although the Internet has become the essence of communication, from an advertiser’s perspective digital advertising remains underexplored. This paper examines the effects of digital media buying efforts on advertisers in Bosnia and Herzegovina, while looking into the methodology of digital media usage behind the actual effects. A combination of secondary research analysis and qualitative research techniques was used. The empirical part is based on in-depth interviews with advertisers and representatives from the digital advertising industry.Perceptions and knowledge of digital advertising are the key drivers for a successful implementation of digital media buying, and advertisers in Bosnia and Herzegovina are aware of its most distinctive qualities. The success of the media buying campaigns relies on brand objectives and choosing the means suited for fulfilling the given goals, which in turn leads to the findings that the focus of companies’ strategies is directed towards the cost-efficient medium usage, rather than solely performance-oriented ones. Measurement of the effects and return on the investment depends on the success of setting up a goal and isolating digital from other marketing efforts.